Functional Network Connectivity Reveals the Brain Functional Alterations in Breast Cancer Survivors - Bukkieva, Tatyana; Pospelova, Maria; Efimtsev, Aleksandr; Fionik, Olga; Alekseeva, Tatyana; Samochernych, Konstantin; Gorbunova, Elena; Krasnikova, Varvara; Makhanova, Albina; Levchuk, Anatoliy; Trufanov, Gennadiy; Combs, Stephanie; et al. (Journal of Clinical Medicine, 2022)
Different neurological and psychiatric disorders such as vertebrobasilar insufficiency, chronic pain syndrome, anxiety, and depression are observed in more than 90% of patients after treatment for breast cancer and may cause alterations in the functional connectivity of the default mode network. The purpose of the present study is to assess changes in the functional connectivity of the default mode network in patients after breast cancer treatment using resting state functional magnetic resonance imaging (rs-fMRI). Rs-fMRI was performed using a 3.0T MR-scanner on patients (N = 46, women) with neurological disorders (chronic pain, dizziness, headaches, and/or tinnitus) in the late postoperative period (>12 months) after Patey radical mastectomy for breast cancer. According to the intergroup statistical analysis, there were differences in the functional connectivity of the default mode network in all 46 patients after breast cancer treatment compared to the control group (p < 0.01). The use of rs-fMRI in in breast cancer survivors allowed us to identify changes in the functional connectivity in the brain caused by neurological disorders, which correlated with a decreased quality of life in these patients. The results indicate the necessity to improve treatment and rehabilitation methods in this group of patients.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Breast cancer; Breast cancer treatment; Connectome; Default mode network; Functional MRI; Post-mastectomy pain syndrome